Depressive symptoms are related to asthma control but not self-management among rural adolescents - Patel, Neha B.; Céspedes, Amarilis; Liu, Jianfang; Bruzzese, Jean-Marie (Frontiers in Allergy, 2024)
Background: Depression, a relevant comorbidity with asthma, has been reported to be associated with asthma morbidity. Asthma self-management is essential to asthma control and may be negatively impacted by depression. We examine these associations in rural adolescents, a group with relatively high asthma morbidity and depressive symptoms, a population often ignored in asthma research.We used baseline data from a randomized trial of an asthma intervention for adolescents in rural South Carolina (n=197). Adolescents completed the Center for Epidemiological Studies-Depression (CES-D), three indices of asthma self-managementthe Asthma Prevention Index, the Asthma Management Index and the Asthma Self-Efficacy Indexand the Asthma Control Test (ACT). Poisson and linear regression tested associations between depression, self-management, and asthma control. Models controlled for demographic variables and school as a fixed effect.Results: Most participants (mean age=16.3±1.2) self-identified as female (68.5%) and Black (62.43%). Mean CES-D score was 19.7±10.3, with 61.4% of participants at-risk for depression.Depressive symptoms were significantly related to asthma control (= -0.085, 95% Confidence Interval (CI)= -0.14, -0.03), but not to prevention (relative risk (RR)=1.00, 95% CI=0.99, 1.01), management (RR=1.00, 95% CI= 0.99, 1.01) or self-efficacy (= -0.002, 95% CI= -0.01, 0.01),In this sample of rural adolescents, as depressive symptoms increased, asthma control declined. Depressive symptoms were not associated with asthma self-management, suggesting that aspects of self-management we assessed are not an avenue by which depression impacts asthma control. Additional research is needed to further understand the relationship between depressive symptoms, asthma self-management and control.Depressive Symptoms Are Related to Asthma Control but Not Self-management Among